2018
DOI: 10.1038/s41598-018-26845-z
|View full text |Cite
|
Sign up to set email alerts
|

First characterization of a microsporidial triosephosphate isomerase and the biochemical mechanisms of its inactivation to propose a new druggable target

Abstract: The microsporidia are a large group of intracellular parasites with a broad range of hosts, including humans. Encephalitozoon intestinalis is the second microsporidia species most frequently associated with gastrointestinal disease in humans, especially immunocompromised or immunosuppressed individuals, including children and the elderly. The prevalence reported worldwide in these groups ranges from 0 to 60%. Currently, albendazole is most commonly used to treat microsporidiosis caused by Encephalitozoon speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 52 publications
4
20
0
Order By: Relevance
“…From the chromatogram obtained for the markers (gel filtration standard # 151-1901 from Bio-Rad), we found that protein mass of the FoxTPI protein corresponds to the native dimers with a relative molecular weigth (MW) of 56 kDa ( Figure 4B), and which is in accordance with the MW expected from the amino acid sequence (27,000 × 2 = 54 kDa), whereas the sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis revealed a unique band of around 27 kDa (Figure 3). This result is consistent with those reported for other TPIs, such as of Saccharomyces cerevisiae [44], and parasites as Entamoeba histolytica (EhTPI), Trypanosoma brucei (TbTPI), T. cruzy (TcTPI), and Encephalitozoon intestinalis (EiTPI), which were reported with a molecular mass around 27 kDa [45][46][47][48].…”
Section: Oligomeric Status Of the Foxtpi Proteinsupporting
confidence: 92%
See 2 more Smart Citations
“…From the chromatogram obtained for the markers (gel filtration standard # 151-1901 from Bio-Rad), we found that protein mass of the FoxTPI protein corresponds to the native dimers with a relative molecular weigth (MW) of 56 kDa ( Figure 4B), and which is in accordance with the MW expected from the amino acid sequence (27,000 × 2 = 54 kDa), whereas the sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis revealed a unique band of around 27 kDa (Figure 3). This result is consistent with those reported for other TPIs, such as of Saccharomyces cerevisiae [44], and parasites as Entamoeba histolytica (EhTPI), Trypanosoma brucei (TbTPI), T. cruzy (TcTPI), and Encephalitozoon intestinalis (EiTPI), which were reported with a molecular mass around 27 kDa [45][46][47][48].…”
Section: Oligomeric Status Of the Foxtpi Proteinsupporting
confidence: 92%
“…The result obtained show that the FoxTPI protein is a well-folded protein with a secondary structure like that of a canonical TPI barrel. It is important to mention that the intensity pattern in the far UV region shown for FoxTPI is similar to to other secondary structures of TPIs previously purified and characterized, as in G. lamblia (GlTPI) [17], human (HuTPI) [50], Trichomonas vaginalis (TvTPI) [55], Saccharomyces cerevisiae (TPI) [44], and Encephalitozoon intestinalis (EiTPI) [48], between which no significant differences were observed.…”
Section: Circular Dichroism (Cd) Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, we propose a potential site as a therapeutic target against the enzyme triosephosphate isomerase for drug development, and that this potential new drug could be safe to be used at humans. We determined the K in position 214 (near the sequence YGGSV−K214) is indispensable for the interaction with the tested compounds and it helps the interaction in the active site from TIM.…”
Section: Introductionmentioning
confidence: 99%
“…The infection prevalence in human populations varies from 0% to 60% worldwide, including ranges of 2.5% to 42%, 1.38% to 13%, 5.2% to 58.1%, and 1.5% to 60% in Europe, Asia, Africa, and the United States respectively (García‐Torres et al. ; Jimenez‐Gonzalez et al. ).…”
mentioning
confidence: 99%